"One-for-All" strategy to design oxygen-deficient triple-shelled MnO2 and hollow Fe2O3 microcubes for high energy density asymmetric supercapacitors. Issue 24 (20th May 2019) - Jia, Henan; Liang, Haoyan; Wang, Zhaoyue; Li, Chun; Zheng, Xiaohang; Cai, Yifei; Qi, Junlei; Cao, Jian; Feng, Jicai; Fei, Weidong
Abstract : Intrinsically poor conductivity, sluggish ion transfer kinetics, and limited specific area are the three main obstacles that confine the electrochemical performance of metal oxides in supercapacitors. Abstract : Intrinsically poor conductivity, sluggish ion transfer kinetics, and limited specific area are the three main obstacles that confine the electrochemical performance of metal oxides in supercapacitors. Engineered hollow metal oxide nanostructures can effectively satisfy the increasing power demand of modern electronics. In this work, both triple-shelled MnO2 and hollow Fe2 O3 microcubes have been synthesized from a single MnCO3 template. The oxygen vacancies are introduced in both the positive and negative electrodes through a facile method. The oxygen vacancies can not only improve the conductivity and facilitate ion diffusion but also increase the electrode/electrolyte interfaces and electrochemically active sites. Consequently, both the oxygen-deficient triple-shelled MnO2 and hollow Fe2 O3 exhibit larger capacitance and rate capability than the samples without oxygen vacancies. Moreover, due to the matchable specific capacitance and potential window between the positive and negative electrodes, the asymmetric supercapacitor exhibits high specific capacitance (240 F g −1 ), excellent energy density of 133 W h kg −1 at 1176 W kg −1, excellent power density (23 529 W kg −1 at 73 W h kg −1 ), and high cycling stability (90.9% after 5000 cycles). This strategy is highly reproducible in oxide-based electrodes, which have the potential to meet the requirements of practical application.